Examining the Influence of Liquidity on Tax Avoidance: The Role of Capital Structure in Indonesian Sharia Banks (2019-2023) - Sahabuddin, Romansyah; Arif, Hery Maulana; Putri, Alya Fadiyah Dwi; Irwan, Shabrina Nurfadhilah; Sofyan, Safira Ainun Nadira (International Humanity Advance, Business & Sciences, 2024)
This research investigates the effect of liquidity on tax avoidance, considering capital structure as an intervening variable, with a focus on banking companies listed on the Indonesia Stock Exchange (IDX). The independent variable analyzed is liquidity, measured by the Loan to Deposit Ratio (LDR), while tax avoidance serves as the dependent variable, represented by the Effective Tax Rate (ETR). The capital structure, acting as the intervening variable, is assessed using the Debt to Equity Ratio (DER). The study population comprises all banking companies listed on the IDX during the period from 2019 to 2023. A quantitative approach is utilized, employing purposive sampling to select 10 banking companies that satisfy the relevant criteria for the study. Data analysis is performed using Partial Least Squares (PLS) through the SmartPLS version 4.0 software. The findings indicate that: 1) Liquidity has a significant effect on tax avoidance; 2) Liquidity significantly influences capital structure; 3) Capital structure positively affects tax avoidance; and 4) Liquidity significantly impacts tax avoidance through capital structure.